AI-Mediated Discourse in Arabic Grammar Acquisition: Linguistic Interaction Patterns in ChatGPT-Assisted Nahwu Learning - Tamim Mulloh; M. Abdul Hamid; Ahmad Mubaligh (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2026)
This study investigates discourse dynamics emerging when undergraduate students engage ChatGPT as an interlocutor in classical Arabic grammar (nahwu) learning, examining how such engagement alters academic discourse structure in an Islamic university. An explanatory sequential mixed-methods design was adopted with 34 students at UIN Maulana Malik Ibrahim Malang—17 in a ChatGPT-integrated class and 17 in a conventional class. Pre- and post-tests of nahwu competence were analyzed using Paired Sample T-Test, Independent Sample T-Test, and Cohen’s d. Classroom observations and semi-structured interviews provided qualitative data, analyzed thematically. ChatGPT-assisted learners demonstrated significantly stronger grammatical gains (p 0.05; Cohen’s d = 2.9), while qualitative data revealed a clear shift from passive teacher-centered discourse toward student-driven analytical dialogue. These results illuminate how AI-mediated interaction reshapes the pragmatic and interactional conditions of second-language grammar acquisition.